Algebras of block Toeplitz matrices with commuting entries. Issue 14 (26th October 2021) - Khan, Muhammad Ahsan; Timotin, Dan
Abstract : The maximal algebras of scalar Toeplitz matrices are known to be formed by generalized circulants. The identification of algebras consisting of block Toeplitz matrices is a harder problem that has received little attention up to now. We consider the case when the block entries of the matrices belong to a commutative algebra A . After obtaining some general results, we classify all the maximal algebras for certain particular cases of A .